Roasting effect on the electrical resistivity of the Al-0,5%Zr alloys - Smagulov, D.U.; Belov, N.A.; Dostayeva, A.M. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The effect of regimes of deformation and heat treatment on electrical resistivity and vickers hardness of 2 aluminum alloys containing 0.2% Zr and 0.4% Zr (mass%) was studied. Flat ingots (10х40х200 mm and 40х120х200 мм) were produced by casting into a graphite moulds. ingots were hot and cold rolled to obtain sheets (thickness 1.3 mm and 5 mm for cold rolled and hot rolled accordingly). Ingots and sheets were annealed according to multistage modes in the temperature range 200–650 °C with a step of 50 °C and 3 h holding at each stage. Polished samples cut from the central part of the ingots (as-cast and annealed) were studied. the structure was examined in optical (om, axiovert 200 mmat) and electron scanning electron (tescan vega 3) microscopes. Thin foils for transmission electron microscopy (tem) were prepared by electrolitic thinning in a perchloric acid–alcohol solution and studied at 160 kv.
Al-0,5%Zr қорытпаларының электр кедергісіне күйдірудің əсері
Влияние обжига на удельное электрическое сопротивление Al-0,5%Zr сплавов
Keywords: aluminum alloys; system Al–Zr; phase Al3Zr; electrical resistivity; deformation and heat treatment; hardening and softening